2015
DOI: 10.1007/s10637-015-0298-3
|View full text |Cite
|
Sign up to set email alerts
|

A phase I trial of mFOLFOX6 combined with the oral PI3K inhibitor BKM120 in patients with advanced refractory solid tumors

Abstract: Summary Purpose The oral PI3K inhibitor BKM120 has been reported as safe and well tolerated in early phase clinical trials of advanced cancer patients. We performed a phase I trial of BKM120 plus mFOLFOX6 (5-FU/LV + oxaliplatin), a common chemotherapeutic backbone in GI malignancies, to establish the maximum tolerated dose (MTD) and characterize the safety and tolerability of the combination. Methods Patients with advanced solid tumors received oral BKM120 daily combined with standard doses of mFOLFOX6 ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 15 publications
0
31
0
Order By: Relevance
“…Studies have shown that targeted therapy on JAK2/STAT3 or PI3K/Akt pathway could be effective for several cancers, such as endometrial cancer and ovarian cancer 4345. Researchers have reported that the resistance of CCA to chemotherapy could be related to the PI3K/Akt signaling, and that targeted inhibition on PI3K/Akt signaling pathway may increase sensitivity to chemotherapeutic agents 46. In addition, it has been reported that CTS could reverse chemotherapy resistance in colon cancer and lung cancer cells 47,48.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that targeted therapy on JAK2/STAT3 or PI3K/Akt pathway could be effective for several cancers, such as endometrial cancer and ovarian cancer 4345. Researchers have reported that the resistance of CCA to chemotherapy could be related to the PI3K/Akt signaling, and that targeted inhibition on PI3K/Akt signaling pathway may increase sensitivity to chemotherapeutic agents 46. In addition, it has been reported that CTS could reverse chemotherapy resistance in colon cancer and lung cancer cells 47,48.…”
Section: Discussionmentioning
confidence: 99%
“…The MTD was 80 mg/d in a phase I study of buparlisib in patients with advanced acute leukemias [109]. A phase I trial in patients with advanced solid tumors suggested that the MTD of buparlisib in combination with standard doses of mFOLFOX6 (every 2 weeks of a 28-day cycle) was 40 mg daily; increased toxicity was observed compared to that expected from either buparlisib or mFOLFOX6 alone [110]. This trial concluded that further studies of buparlisib in combination with mFOLFOX6 are not recommended in gastrointestinal tumor.…”
Section: Pf-04691502 and Pf-05212384 (Gedatolisib Pki-587)mentioning
confidence: 99%
“…More recently, increased efficacy was attained in-vitro by dual inhibition of the PI3K/AKT/MTOR and RAF/MEK/ERK pathway, which overcame resistance pathways [74]. A phase I trial of mFOLFOX6 and the oral PI3K inhibitor BKM120 in patients with advanced solid tumors (4/17 CCA) reported high toxicity rates, with 76 % of the patients experiencing a grade 3/4 AE [75]. The most common AEs were neutropenia, fatigue, leukopenia, hyperglycemia and thrombocytopenia.…”
Section: Less-established Molecular Aberrationsmentioning
confidence: 99%